Weber e o Desencantamento do Mundo: Uma Interlocução com o Pensamento de Nietzsche - Renarde Freire Nobre (Universidade do Estado do Rio de Janeiro, 2006)
This article conducts a theoretical confrontation between the thinking of Max Weber and that of Friedrich Nietzsche concerning the modernWestern world, based on the notions of "death of God" and "disenchantment of the world". The article explores the affinities and differences between the two thinkers, especially from the angle of Weber´s diagnosis of the "culture of technique" and its inexorable effects on subjectivity. The paper´s underlying hypothesis is that despite the parallels that can (and should) be drawn between the two, what prevails is an insurmountable distance, especially by the recognition of the powers of reason and the vision of a cultural world edified under the command of conscious orientations.